Pleomorphic adenoma of the base tongue - Gupta, Manish (Springer-Verlag, 2007)
Pleomorphic adenoma is the benign tumor of salivary glands. The cells of origin are the myoepithelial cells and intercalated duct cells. This tumor is more common in major salivary glands. A rare case of pleomorphic adenoma of the minor salivary glands of base tongue is reported here. It was surgically excised by a median mandibulotomy approach and patient is free of any recurrence in one-year follow-up.